HRM practices and turnover intention: the mediating effect of work engagement in the food and beverage industry in Indonesia - Dinar Rurumingratni; Aryana Satrya (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This study examines the impact of human resource management (HRM) practices (i.e., training and pay satisfaction) on turnover intentions mediated by work engagement among employees in the food & beverage industry in Indonesia. Based on National Labor Force Survey in February 2021, the accommodation, the food & beverage industry is the fourth largest contributor to employment in Indonesia, which is 6.99%. This study uses a multidimensional approach for HRM practices, work engagement, and turnover intention. This approach shows how HRM practices affect the formation of work engagement. Data were collected through online questionnaires and analyzed using the partial least squares structural equation modeling (PLS-SEM) technique. Findings revealed that training satisfaction and pay satisfaction have a significant positive impact on work engagement, and pay satisfaction has a negative impact on turnover intention. Unexpectedly, training satisfaction has a positive impact on turnover intention. However, this study did not find sufficient evidence for the direct impact of work engagement on turnover intention and the effect of training and pay satisfaction on turnover intention mediated by work engagement. Therefore, employees who are satisfied with their training and pay schemes will engage with their work and tend not to leave their jobs. Further study may apply more respondents, as well as investigates other variables of HRM practices examined. The results of this study can be used to enrich existing knowledge and assist company management in formulating HRM strategies to create work engagement among employees.